Contribuição dos fungos micorrízicos arbusculares na indução à resistência do tomateiro a Meloidogyne incognita raça 2. - Freitas, Emanuel Dias (2013)
Studies mycorrhizal fungi try to elucidate the contribution of microorganisms in the transport of signaling between plants compounds, since they form a network that connects the underground mycelial and plant substances are able to translocate between neighboring plants. The aim of this study was to evaluate the contribution of mycorrhizal fungi in inducing resistance of tomato to Meloidogyne incognita race 2. The experiment was conducted in a greenhouse and the experimental design was a completely randomized design, consisting of 4 treatments and 5 replicates, totaling 20 plots. Each plot was constituted by a dual system connected initial vessel containing a plant on each side of the vessel, where a plant has been called issuing (I) and one receiver (R).The treatments were derived from the combination of the potted issuing plants with and without mycorrhiza, respectively (IM + and IM-) connected the potted receiver plant with and without mycorrhiza (RM + and RM-). The experiment was conducted in two phases, phase I and phase II. It started with phase I the introduction of nematode inoculum (4000 eggs and J2 Meloidogyne incognita race 2) only at the sides of the pots containing the issuing plants with and without mycorrhiza (IM + and IM-), and those remained in contact with nematodes for 45 days. After this period, we proceeded to double the separation vessel connected. Phase II began after the separation vessel and addition of the nematode inoculum in receiver plants 45 days remaining in contact with the nematodes in the greenhouse. The results showed that issuing plants inoculated with mycorrhizal were more likely to parasitism by M. incognita race 2, with lower plant development and increased susceptibility to nematodes. The receiver plants that were in contact with the issuing plants with mycorrhiza (IM+) during the preconditioning showed better growth and lower susceptibility to M. incognita revealing thereby that were stimulated during Phase I, the activate mechanism of defense against the pathogen.